Rietveld texture analysis from synchrotron diffraction images. II. Complex multiphase materials and diamond anvil cell experiments. Issue 3 (15th May 2014) - Wenk, Hans-Rudolf; Lutterotti, Luca; Kaercher, Pamela; Kanitpanyacharoen, Waruntorn; Miyagi, Lowell; Vasin, Roman
Abstract : Synchrotron X-ray diffraction images are increasingly used to characterize crystallographic preferred orientation distributions (texture) of fine-grained polyphase materials. Diffraction images can be analyzed quantitatively with the Rietveld method as implemented in the software package Materials Analysis Using Diffraction. Here we describe the analysis procedure for diffraction images collected with high energy X-rays for a complex, multiphase shale, and for those collected in situ in diamond anvil cells at high pressure and anisotropic stress.